2006
DOI: 10.1007/s11243-006-0008-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Spectrothermal Studies of Thermochromic Diamine Complexes of Cobalt(III), Nickel(II) and Copper(II) Squarate. Crystal Structure of [Co(en)3](sq)1.5 · 6H2O

Abstract: New adducts of ethylenediamine (en), N,N-dimethylethylenediamine (ndmen) and N,N¢-dimethylethylenediamine (dmen) with squarate as counter-ions were synthesized and characterized by physico-chemical methods (IR and UV/ vis spectroscopy, magnetic susceptibility and thermoanalytical measurements). The crystal structure of tris(ethylenediamine)cobalt(III) 1.5 squarate hexahydrate, [Co(en) 3 ](sq) 1.5 AE 6H 2 O, was determined by single crystal X-ray diffraction. Co(III), Ni(II) and Cu(II) ions in the monomeric oct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The free ligand showed a strong band characteristic of the azomethine ν(C═ N) group at 1617 cm −1 , which was diagnostic for Schiff base condensation, while no bands attributable to C═ O group were detected. The two bands at 3467 and 3352 cm −1 were attributed to the ν(NH 2 ) mode of diamines . The chelation of the Schiff base ligand could be easily detected by monitoring the position of the ligand bands which shifted to lower or higher energy upon complexation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The free ligand showed a strong band characteristic of the azomethine ν(C═ N) group at 1617 cm −1 , which was diagnostic for Schiff base condensation, while no bands attributable to C═ O group were detected. The two bands at 3467 and 3352 cm −1 were attributed to the ν(NH 2 ) mode of diamines . The chelation of the Schiff base ligand could be easily detected by monitoring the position of the ligand bands which shifted to lower or higher energy upon complexation.…”
Section: Resultsmentioning
confidence: 99%
“…The two bands at 3467 and 3352 cm −1 were attributed to the ν(NH 2 ) mode of diamines. [37] The chelation of the Schiff base ligand could be easily detected by monitoring the position of the ligand bands which shifted to lower or higher energy upon complexation. For all complexes, the ν(C═ N) band underwent a change in frequency and intensity, caused by complexation, shifted by 2-10 cm −1 to higher frequency.…”
Section: Ft-ir Spectramentioning
confidence: 99%
“…Copper(II) and nickel(II) complexes with the bidentate diamine ligand were studied extensively due to their thermochromic properties [7][8][9][10][11][12][13][14][15]. The investigations revealed that the nature of the diamine ligand and counter anion are crucial for the thermochromism.…”
Section: Introductionmentioning
confidence: 99%
“…The absorption band at 1049 cm -1 is due the C-C vibration. [35,53] The weak band at 889 cm -1 is mainly caused by the peroxo group. [54,55] , and 542 nm (band III).…”
Section: Resultsmentioning
confidence: 99%
“…Supramolecular structures, in which the squarate dianion acts as a counterion were found using N-donor ligands. [24][25][26][27][28][29][30][31][32][33][34] Yesilel et al [35] reports on the reaction of cobalt(II) squarate with ethylenediamine (en) at elevated temperature leading to a tris(ethylenediamine)cobalt(III) squarate, in which the squarate dianions act exclusively as counterions and hydrogen bonds between the anions and the complex [Co(en)] 3+ cations build up a three-dimensional supramolecular network.…”
Section: Introductionmentioning
confidence: 99%